ANTIBIOTIC PROPHYLAXIS IN DENTAL SURGERY - Furkatov Shokhjakhon, Latipov Jurabek, Odilov Bakhodir, Mustafoyev Aziz (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Briefly formulating modern ideas about the preventive use of antibiotics, it is necessary to proceed from three general cases of antibiotic prophylaxis: 1) to prevent infection with exogenous pathogens; 2) to prevent the spread of resident microflora from some parts of the body to others, normally sterile; 3) to prevent the development of diseases with latent infections. Antibiotic prophylaxis in surgery is usually justified only when postoperative infection in the wound is highly likely or may have severe consequences. First of all, such conditions can occur when the mucous membrane is dissected, in particular in the oral cavity, which limits the numerous populations of resident bacteria, which cause contamination of the wound [1, 4, 5, 10]. This article presents up-to-date information on antibiotic prophylaxis of the development of postoperative infection, discusses effective schemes for the preventive use of inhibitor-protected aminopenicillin using the example of a combination of amoxicillin with clavulanic acid for the removal of retarded dystopian third lower molars, dental implantation, sinus lifting with anthropoplasty to reduce the risk of postoperative infectious complications.